Estudio de prefactibilidad para la instalación de una planta de producción de cerveza artesanal a base de maíz malteado - Heros Callirgos, Maria Fernanda (2022)
For this project, the first chapter will present the topic, the objectives of the research both general and specific, the justification and hypothesis of the work. In the second chapter, the entire study of the market will be developed, starting with the definition of the product, the geographical area, the potential demand and its projection will be defined. In the third chapter, the macro and micro factors will be analyzed to make an optimal choice of the location of the craft beer production plant based on malted corn. In the fourth chapter, the type of technology to be used for the production processes will be defined, the machinery and equipment to be used will be detailed, in order to carry out the plant capacity. In addition, there will be a quality evaluation of the main inputs, environmental impact studies and safety methods to protect workers.